Study of tauopathies by comparing Drosophila and human tau in Drosophila. - Chen, X.; Li, Y.; Huang, J.; Cao, D.; Yang, G.; Liu, W.; Lu, H.; Guo, A. (Cell and Tissue Research, 2007)
The microtubule-binding protein tau has been investigated for its contribution to various neurodegenerative disorders. However, the findings from transgenic studies, using the same tau transgene, vary widely among different laboratories. Here, we have investigated the potential mechanisms underlying tauopathies by comparing Drosophila (d-tau) and human (h-tau) tau in a Drosophila model. Overexpression of a single copy of either tau isoform in the retina results in a similar rough eye phenotype. However, co-expression of Par-1 with d-tau leads to lethality, whereas co-expression of Par-1 with h-tau has little effect on the rough eye phenotype. We have found analogous results by comparing larval proteomes. Through genetic screening and proteomic analysis, we have identified some important potential modifiers and tau-associated proteins. These results suggest that the two tau genes differ significantly. This comparison between species-specific isoforms may help to clarify whether the homologous tau genes are conserved.